Implementasi Qawaid Fiqhiyyah Dalam Ekonomi Dan Industri Keuangan Syariah - Irwan Maulana (STAI Asy-Syukriyyah, 2018)
The existence of Islamic Principles of Jurisprudences (qawa'id fiqhiyyah) is to provide a more practical guide derived from the original text, namely al-Qur'an and al- Hadith to the community. With this, some theologians (ulama) can prepare life guidelines for Muslims in different spheres from time to time and place to place. As is known, Islam gives its people the opportunity through those who have the authority to carry out ijtihad in various ways guided by the Messenger of Allah, through ijma', qiyas, istihsan, istishab, istislah (masalihul-mursalah) and so on to look for truth that has not been explained in detail in the Qur'an and the Hadith of the Muhammad SAW. Likewise, in economic life, or in the treasury of the works of earlier fuqaha commonly called muamalah, the use of qawa'id fiqhiyyah becomes very important.